Adventures in Shondaland Identity Politics and the Power of Representation - Griffin, Rachel Alicia; Meyer, Michaela D.E (Rutgers University Press, 2018)
Shonda Rhimes is one of the most powerful players in contemporary American network television. Beginning with her break-out hit series Grey’s Anatomy, she has successfully debuted Private Practice, Scandal, How to Get Away with Murder, The Catch, For The People, and Station 19. Rhimes’s work is attentive to identity politics, "post-" identity politics, power, and representation, addressing innumerable societal issues. Rhimes intentionally addresses these issues with diverse characters and story lines that center, for example, on interracial friendships and relationships, LGBTIQ relationships and parenting, the impact of disability on familial and work dynamics, and complex representations of womanhood. This volume serves as a means to theorize Rhimes’s contributions and influence by inspiring provocative conversations about television as a deeply politicized institution and exploring how Rhimes fits into the implications of twenty-first century television